Supplementary weather observation stations / drawn in Geog. Div., C.O.I. - United States. Office of Coordinator of Information. Geography Division (United States. Office of Strategic Services. Geography Division, 1942)
"Map no. 476, April 24, 1942." "Free." Grayscale 1:18,900,000